THE IMPACT OF ENTREPRENEURSHIP EDUCATION ON STUDENT INTENTION: A MEDIATION MODEL INVOLVING SELF-EFFICACY AND SOCIAL PRESSURE IN CHINA PUBLIC UNIVERSITIES - Mu , Zongliang; Che Rusuli, Muhamad Saufi; Nasir, Wan Mohd Nazdrol Wan Mohd; Ridzwan, Rikinorhakis (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
Entrepreneurship education has been widely promoted as a strategic instrument to cultivate entrepreneurial intention among university students; however, empirical findings regarding its effectiveness remain inconclusive, particularly in economically underdeveloped regions. Drawing on the Theory of Planned Behaviour (Ajzen, 1991) and Social Cognitive Theory (Bandura, 1977), this study examines the impact of entrepreneurship education on entrepreneurial intention among students in public universities in Guangxi, China, with self-efficacy and social pressure tested as parallel mediators. Entrepreneurship education is conceptualised as a multidimensional construct comprising entrepreneurial knowledge, entrepreneurial motivation, entrepreneurial role models, entrepreneurial AI skills, and entrepreneurial practice. Using a quantitative cross-sectional design, data were collected from 482 third- and fourth-year undergraduate students. Partial Least Squares Structural Equation Modelling (PLS-SEM) was employed for data analysis. The findings reveal that, except for entrepreneurial knowledge, all dimensions of entrepreneurship education significantly enhance students’ self-efficacy, while all five dimensions positively influence perceived social pressure. Self-efficacy exerts a strong positive effect on entrepreneurial intention and serves as the primary mediating mechanism, whereas social pressure demonstrates a weaker and selective mediating effect. The study contributes to entrepreneurship education literature by validating a dual-mediation model in an underdeveloped regional context and provides policy-relevant implications for optimising entrepreneurship education in Guangxi and similar regions.